Associative and Comparative Study on Students’ Perseverance and Religious in Islamic Education Subject - Amin, Alfauzan; Alimni, Alimni; Perdana, Rahmat Eka; Azzahra, Miftahul Zannah; Septi, Sabila Eka (FKIP Universitas Lampung, 2021)
Associative and Comparative Study on Students’ Perseverance and Religious in Islamic Education Subject. Objective: This study aims to understand the differences and the relationship among student perseverance and student religious in Islamic religious education subjects at MTs 1 Bengkulu City and MTs 1 Jambi City. Methods: This research uses quantitative methods with associative and comparative research types. Findings: The results of the T with a value of sig. (2-tailed < 0.05 and the result of correlation test between students’ perseverance and religious students in Islamic religious education subjects obtained the result of the correlation test with the value of sig. (2-tailed) < 0.05. Conclusion: there is a difference and relationship between students’ perseverance and religious students in Islamic religious education subjects at MTs 1 Bengkulu City and MTs 1 Jambi City. Keywords: perseverance, religious, islamic education.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202119